Curriculum Klinische Akut- und Notfallmedizin – Schwerpunkt Innere Medizin: Empfehlung zu Weiterbildungsinhalten der Inneren Medizin in der Notaufnahme - Busch, Hans Jörg; Wolfrum, Sebastian; Michels, Guido; Baumgärtel, Matthias; Bodmann, Klaus Friedrich; Buerke, Michael; Burst, Volker; Enghard, Philipp; Ertl, Georg; Fach, Wolf Andreas; Hanses, Frank; Heppner, Hans Jürgen; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2024)
In Germany, physicians qualify for emergency medicine by combining a specialty medical training—e.g. internal medicine—with advanced training in emergency medicine according to the statutes of the State Chambers of Physicians largely based upon the Guideline Regulations on Specialty Training of the German Medical Association. Internal medicine and their associated subspecialities represent an important column of emergency medicine. For the internal medicine aspects of emergency medicine, this curriculum presents an overview of knowledge, skills (competence levels I–III) as well as behaviours and attitudes allowing for the best treatment of patients. These include general aspects (structure and process quality, primary diagnostics and therapy as well as indication for subsequent treatment; resuscitation room management; diagnostics and monitoring; general therapeutic measures; hygiene measures; and pharmacotherapy) and also specific aspects concerning angiology, endocrinology, diabetology and metabolism, gastroenterology, geriatric medicine, hematology and oncology, infectiology, cardiology, nephrology, palliative care, pneumology, rheumatology and toxicology. Publications focussing on contents of advanced training are quoted in order to support this concept. The curriculum has primarily been written for internists for their advanced emergency training, but it may generally show practising emergency physicians the broad spectrum of internal medicine diseases or comorbidities presented by patients attending the emergency department.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Advanced training “Clinical Acute- and Emergency Medicine”; Advanced training “Emergency Medicine”; German Medical Association; German Society of Internal Medicine (DGIM); German Society of Medical Intensive Care and Emergency Medicine (DGIIN); Professional Association of German Internists (BDI); Resuscitation room management